Sustainability and Capital Structure: Financial Performance in Logistics Companies - Nurmaria Sarosa; Edhie Budi Setiawan; Nofrisel Nofrisel; Okin Purba (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The logistics and transportation sector plays a critical role in global and national supply chains but is also characterized by high energy consumption and environmental emissions. Despite the increasing adoption of Environmental, Social, and Governance (ESG) practices, empirical evidence on their financial implications in Indonesian logistics companies remains limited. This study examines the impact of ESG performance on corporate financial performance, measured by Return on Assets (ROA) and Return on Equity (ROE), with capital structure (Debt-to-Equity Ratio) as a control variable. Using panel data from 44 listed logistics companies in Indonesia over the period 2019–2023, this research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) and multigroup analysis to compare national and multinational firms. The results indicate that environmental performance has a positive and significant effect on ROA, while social performance positively influences ROE. Conversely, governance performance shows a negative association with ROE, suggesting potential compliance and administrative cost trade-offs. The capital structure variable does not significantly affect financial performance. Furthermore, the ESG–financial performance relationship is stronger among multinational companies compared to national firms. These findings contribute to the sustainability accounting and corporate governance literature by demonstrating that selective ESG integration creates financial value in the logistics sector, particularly through environmental and social initiatives, while governance mechanisms should be implemented efficiently to avoid reducing operational and financial flexibility. The study provides implications for regulators, corporate managers, and investors in strengthening ESG-based financial and reporting strategies in emerging markets. Keywords: Environmental, Social, Governance, Financial Performance, Logistics Companies